Дослідження сорбції тетраалкільних похідних калікс[4]аренів і калікс[4]резорцинаренів з поверхнею LiChrosorb RP 18 методами ОФ ВЕРХ та молекулярного моделювання - Kalchenko, O. I.; Cherenok, S. O.; Savonik, L. I.; Solovyov, A. V.; Gorbachuk, V. V.; Kalchenko, V. I. (National University of Pharmacy, 2014)
Tetrahydroxycalix[4]arene, tetraalkoxycalix[4]arenes and tetraalkylcalix[4]resorcinarenes are capable to reversible adsorption on the surface of the hydrophobic support LiChrosorb RP 18 under conditions of the reversed-phase high performance liquid chromatography. The main chromatographic characteristics of tetrahydroxycalix[4]arene, a series of tetraalkoxycalix[4]arenes and tetraalkylcalix[4]resorcinarenes have been determined. It has been found that in the conditions selected (the mobile phase is acetonitrile/water, 86/14, v/v) the retention times of the compounds studied are in the wide range from 4.67 min to 88.0 min depending on the nature of the substituents in the macrocyclic skeleton of the molecule. Thus, the retention times increase with increase of the length of the alkyl substituents at the lower rim of the calixarene macrocycle. According to the molecular modelling data the most effective sorption is explained by the inclusion of LiChrosorb RP 18 octadecyl groups into the lipophilic cavity formed by the alkyl substituents at the lower rim of the macrocycle of calixarene/calixresorcinarene. Thus, the molecular cavity formed by the benzene rings remains opened for the Host-Guest complexation with the analyte molecules. This sorption of tetraalkoxycalix[4]arenes and tetraalkylcalix[4]arenes on the LiChrosorb RP 18 surface can significantly improve its resolution ability in RP HPLC analysis. The influence of replacement of tetrahydroxycalix[4]arene hydroxyl protons with the alkyl groups on the conformation of the macrocycle has been studied.